MicroRNAs and Natural Compounds Mediated Regulation of TGF Signaling in Prostate Cancer - Javed, Zeeshan; Khan, Khushbukhat; Rasheed, Amna; Sadia, Haleema; Raza, Shahid; Salehi, Bahare; Cho, William C.; Sharifi-Rad, Javad; Koch, Wojciech; Kukula-Koch, Wirginia; Głowniak-Lipa, Anna; Helon, Paweł (Frontiers in Pharmacology, 2021)
Prostate cancer (PCa) is with rising incidence in male population globally. It is a complex anomaly orchestrated by a plethora of cellular processes. Transforming growth factor-beta (TGF-β) signaling is one of the key signaling pathways involved in the tumorigenesis of PCa. TGF-β signaling has a dual role in the PCa, making it difficult to find a suitable therapeutic option. MicroRNAs (miRNAs) mediated regulation of TGF-β signaling is responsible for the TGF-ß paradox. These are small molecules that modulate the expression of target genes and regulate cancer progression. Thus, miRNAs interaction with different signaling cascades is of great attention for devising new diagnostic and therapeutic options for PCa. Natural compounds have been extensively studied due to their high efficacy and low cytotoxicity. Here, we discuss the involvement of TGF-ß signaling in PCa with the interplay between miRNAs and TGF-β signaling and also review the role of natural compounds for the development of new therapeutics for PCa.